Role of Inflammation in the Pathogenesis of Atrial Fibrillation - Ihara, Kensuke; Sasano, Tetsuo (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) is one of the most common arrhythmias encountered in clinical practice. AF is a major risk factor for stroke, which is associated with high mortality and great disability, and causes a significant burden on society. With the development of catheter ablation, AF has become a treatable disease, but its therapeutic outcome has been limited so far. In persistent and long-standing AF, the expanded AF substrate is difficult to treat only by ablation, and a better understanding of the mechanism of AF substrate formation will lead to the development of a new therapeutic strategy for AF. Inflammation is known to play an important role in the substrate formation of AF. Inflammation causes and accelerates the electrical and structural remodeling of the atria via pro-inflammatory cytokines and other inflammatory molecules, and enhances the AF substrate, leading to the maintenance of AF and further inflammation, which forms a vicious spiral, so-called “AF begets AF”. Breaking this vicious cycle is expected to be a key therapeutic intervention in AF. In this review, we will discuss the relationship between AF and inflammation, the inflammatory molecules included in the AF-related inflammatory process, and finally the potential of those molecules as a therapeutic target.